Archaeology in the digital era : papers from the 40th Annual Conference of Computer Applications and Quantitative Methods in Archaeology (CAA), Southampton, 26-29 March 2012 - Earl, Graeme, (Computer applications and quantitative methods in archaeology., 2012)
CAA is the foremost conference on digital archaeology, and this volume offers a comprehensive and up-to date reference to the state of the art. This volume contains a selection of the best papers presented at the 40th Annual Conference of Computer Applications and Quantitative Methods in Archaeology (CAA), held in Southampton from 26 to 29 March 2012. The papers, all written and peer-reviewed by experts in the field of digital archaeology, explore a multitude of topics to showcase ground-breaking technologies and best practice from various archaeological and informatics disciplines, with a variety of case studies from all over the world. Download the Table of Contents and a sample chapter